The development of interactive mobile learning media for Egrang Batok dance to improve learning outcomes - Utami, Arinta Widya Kasi; Nurharini, Atip (Jurnal Prima Edukasia, 2026)
The lack of innovative technology-based learning media significantly impacts student learning outcomes. This study aimed to develop practical, feasible, and effective mobile learning media for fourth-grade elementary school dance lessons to enhance academic achievement. The implication of this study is that the learning process becomes more engaging through the integration of technology- based instructional tools. The research utilized the Research and Development (R&D) method with the ADDIE model. The subjects included one subject matter expert, one media expert, one teacher, and 36 fourth-grade students. Data collection techniques included pre- and post-tests, as well as non-test methods such as observation, teacher interviews, documentation, and questionnaires. Data analysis was conducted using the Shapiro-Wilk normality test, T-tests, and N-Gain tests. The feasibility analysis of the TERBATIK media indicated that it was highly feasible, with ratings of 100% from the subject matter expert and 93% from the media expert. Response rates from the teacher and students were 93.7% and 93.1%, respectively, placing them in the highly practical category. The normality test results were normal, with pre-test scores of 0.098 and post-test scores of 0.096 (ρ > 0.05). The effectiveness analysis via the T-test showed a significance value of 0.000 (ρ < 0.05), with the average score increasing from 55.6944 in the pre-test to 87.3611 in the post-test. The N-Gain score was 0.7313, representing the high category. Based on these results, it can be concluded that the TERBATIK media is feasible, practical, and effective in improving the learning outcomes of fourth-grade dance classes. These results imply that integrating mobile learning applications into arts education not only modernizes traditional dance instruction but also provides an accessible, interactive platform that bridge the gap between cultural content and digital-native students.